Tympanic Plate Fractures in Temporal Bone Trauma: Prevalence and Associated Injuries - Wood, C.P.; Hunt, C.H.; Bergen, D.C.; Carlson, M.L.; Diehn, F.E.; Schwartz, K.M.; McKenzie, G.A.; Morreale, R.F.; Lane, J.I. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The prevalence of tympanic plate fractures, which are associated with an increased risk of external auditory canal stenosis following temporal bone trauma, is unknown. A review of posttraumatic high-resolution CT temporal bone examinations was performed to determine the prevalence of tympanic plate fractures and to identify any associated temporal bone injuries. MATERIALS AND METHODS: A retrospective review was performed to evaluate patients with head trauma who underwent emergent high-resolution CT examinations of the temporal bone from July 2006 to March 2012. Fractures were identified and assessed for orientation; involvement of the tympanic plate, scutum, bony labyrinth, facial nerve canal, and temporomandibular joint; and ossicular chain disruption. RESULTS: Thirty-nine patients (41.3 ± 17.2 years of age) had a total of 46 temporal bone fractures (7 bilateral). Tympanic plate fractures were identified in 27 (58.7%) of these 46 fractures. Ossicular disruption occurred in 17 (37.0%). Fractures involving the scutum occurred in 25 (54.4%). None of the 46 fractured temporal bones had a mandibular condyle dislocation or fracture. Of the 27 cases of tympanic plate fractures, 14 (51.8%) had ossicular disruption (P = .016) and 18 (66.6%) had a fracture of the scutum (P = .044). Temporomandibular joint gas was seen in 15 (33%) but was not statistically associated with tympanic plate fracture (P = .21). CONCLUSIONS: Tympanic plate fractures are commonly seen on high-resolution CT performed for evaluation of temporal bone trauma. It is important to recognize these fractures to avoid the preventable complication of external auditory canal stenosis and the potential for conductive hearing loss due to a fracture involving the scutum or ossicular chain. HRCThigh-resolution CTTMJtemporomandibular jointTPFtympanic plate fracture